2016
DOI: 10.1017/s1743921316011261
|View full text |Cite
|
Sign up to set email alerts
|

Star formation at low rates - the impact of lacking massive stars on stellar feedback

Abstract: Due to their low masses dwarf galaxies experience low star-formation rates resulting in stellar cluster masses insufficient to fill the initial mass function (IMF) to the uppermost mass. Numerical simulations usually do not account for the completeness of the IMF, but treat a filed IMF by numbers, masses, and stellar feedback by fractions. To ensure that only entire stars are formed, we consider an IMF filled from the lower-mass regime and truncated where at least one entire massive star is formed.By 3D simula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…They further found that regardless of sampling method, the combined IMF of multiple star particles together will be undersampled below particle masses of ∼10 3 M . Bracketing the case of a stochastic IMF, Hensler et al (2017) compared a truncated and a filled IMF in simulations of dwarf galaxies, and found that truncation suppresses the self-regulation of star formation. Several cosmological simulations have discussed or incorporated methods of discretizing stellar feedback from Type II supernovae (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…They further found that regardless of sampling method, the combined IMF of multiple star particles together will be undersampled below particle masses of ∼10 3 M . Bracketing the case of a stochastic IMF, Hensler et al (2017) compared a truncated and a filled IMF in simulations of dwarf galaxies, and found that truncation suppresses the self-regulation of star formation. Several cosmological simulations have discussed or incorporated methods of discretizing stellar feedback from Type II supernovae (e.g.…”
Section: Introductionmentioning
confidence: 99%